Anti-adipogenic effects of viscothionin in 3T3-L1 adipocytes and high fat diet induced obesity mice - Kim, Sokho; Ahn, Seo-Hyun; Park, Jong-Heum; Park, Chan Hum; Sin, Yu Su; Shin, Gee-Wook; Kwon, Jungkee (Applied biological chemistry, 2020)
Viscum album subsp. Coloratum , also known as Korean mistletoe, is a traditional herb that has more recently been used for the treatment of nervine, hypertensive and cardiovascular diseases. Therefore, this study was undertaken to access the anti-obesity effect of Korean mistletoe-derived polypeptide viscothionin using 3T3-L1 adipocytes in vitro and in vivo mouse experimental model. Viscothionin (up to 5 μM) was used to treat mouse 3T3-L1 pre-adipocytes during adipocyte differentiation. Adipocyte differentiation in 3T3-L1 cells was confirmed by Oil Red O staining. Obesity was induced by a high-fat diet (HFD) in C57BL/6J mice, followed by oral administration of viscothionin (up to 10 mg/kg) for 3 weeks. As a result, viscothionin (5 μM) inhibited differentiation of adipocyte cells and attenuated accumulation of intracellular lipids through activation of 5′-adenosine monophosphate-activated protein kinase (AMPK), by down-regulating phosphorylation in AKT and glycogen synthase kinase 3β (GSK3β). Treatment of viscothionin also decreased the levels of sterol regulatory element binding protein-1 (SREBP-1) and its target gene, fatty acid synthase (FAS). Moreover, viscothionin (10 mg/kg) significantly suppressed body weight and fat content, and improved serum lipid concentration, compared with the standard drug simvastatin (10 mg/kg), a well-known anti-obesity agent. The present study suggests, that viscothionin exerts anti-adipogenic effect through the activation of AMPK and has potential to prevent HFD-induced obesity.